2009
DOI: 10.1111/j.1467-8489.2009.00465.x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling hydroclimatic uncertainty and short‐run irrigator decision making: the Goulburn system*

Abstract: Australia has an incredibly variable and unpredictable hydroclimate, and while irrigation is designed to reduce risk, significant uncertainty remains in both seasonal water availability ('allocations') and irrigation crop water requirements. This paper explores the nature and impacts of seasonal hydroclimatic uncertainty on irrigator decision making and temporary water markets in the Goulburn system in northern Victoria. Irrigation and water trading plans are modelled for the three seasons of the irrigation ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The Goulburn River Basin is located in the south-western part of State Victoria, Australia. The description of the region and a review of the literature devoted to water resource modeling and planning can be found, for instance, in References [18][19][20]. The review of papers on allocation modeling in this region and water trading can be found in References [21][22][23].…”
Section: Numerical Study: Goulburn River Cascadementioning
confidence: 99%
“…The Goulburn River Basin is located in the south-western part of State Victoria, Australia. The description of the region and a review of the literature devoted to water resource modeling and planning can be found, for instance, in References [18][19][20]. The review of papers on allocation modeling in this region and water trading can be found in References [21][22][23].…”
Section: Numerical Study: Goulburn River Cascadementioning
confidence: 99%
“…In water‐scarce areas, hydroclimatic uncertainty is also costly in terms of irrigation decision efficiency (Griffith et al . ). Very often farmers have to make crop and management decisions without knowledge of how much water will be available in the season (Calatrava and Garrido ; Iglesias et al .…”
Section: Introductionmentioning
confidence: 97%
“…As far as we know, by reviewing previous literatures, past researches were mainly focused on using single objective optimization to resolve water allocation problem [7][8][9][10][11]. However, it is hard to make a feasible and reliable water allocation strategy based on only one water objective optimization.…”
Section: Introductionmentioning
confidence: 99%